Opportunities and challenges in India's food export - Saritha S (Yojana)
The food export sector is a significant contributor to India's foreign exchange earning and still holds a huge untapped potential. The food processing industry can tap into that potential with diversified products having longer shelf lives. It can reduce post- harvest losses and generate employment opportunities. Adopting circular economy practices for the food processing industry will ensure its sustainable growth with a minimised environmental footprint and make our products more competitive, demanding global acceptance.
Keywords: food export, agriculture, Agriculture export policy